Phenomenological principles of the understanding of schizophrenia based on Vygotsky - Costa, Eduardo Moura da [UNESP]; Peres, Savio Passafaro [UNESP] (Univ Fed Rio Janeiro, 2018)
The philosophical tradition initiated by Edmund Husserl, phenomenology, and the historical-cultural theory, developed by Vygotsky, break with the idea of consciousness as something closed. Both conceptions provide a rich perspective on the study of psychopathology. In this sense, the aim of the present article is to contrast the descriptions coming from phenomenology with the attempts of explanation of this phenomenon developed by Vygotsky. One of the most accepted positions among contemporary phenomenologists understands this pathology as a disturbance of the self, causing changes in temporality, corporality and social relations. For Vygotsky, schizophrenia stems from the disintegration of the conceptual formation of consciousness. As a result of this, there is a loss in the perception of reality, of others and of one-self. Finally, we will point out some possible links through the contrast of the two approaches to pathogenic states typical of schizophrenia.
Keywords: Phenomenology; Cultural-historical psychology; Schizophrenia